2015
DOI: 10.1001/jamasurg.2014.3160
|View full text |Cite
|
Sign up to set email alerts
|

Association of Postoperative Hyperglycemia With Outcomes Among Patients With Complex Ventral Hernia Repair

Abstract: IMPORTANCE Patients with medically complex conditions undergoing repair of large or recurrent hernia of the abdominal wall are at risk for early postoperative hyperglycemia, which may serve as an early warning for delays in recovery and for adverse outcomes. OBJECTIVE To evaluate postoperative serum glucose level as a predictor of outcome after open ventral hernia repair in patients with major medical comorbidities. DESIGN, SETTING, AND PARTICIPANTS We performed a retrospective medical record review of 172 con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 48 publications
(22 reference statements)
1
15
0
Order By: Relevance
“…Prior to conducting surgery on patients with DM2, preoperative assessment and planning is required to establish a suitable treatment regimen that will minimize the risk of complications [50,51]. Previous studies, in addition to our data, have shown that the period following a surgical procedure is often characterized by hyperglycemia, which results in a greater incidence of complications and higher costs connected to hospitalization [52][53][54].…”
Section: Discussionmentioning
confidence: 72%
“…Prior to conducting surgery on patients with DM2, preoperative assessment and planning is required to establish a suitable treatment regimen that will minimize the risk of complications [50,51]. Previous studies, in addition to our data, have shown that the period following a surgical procedure is often characterized by hyperglycemia, which results in a greater incidence of complications and higher costs connected to hospitalization [52][53][54].…”
Section: Discussionmentioning
confidence: 72%
“…Glycemic control pre-, intra-, and postoperatively has been proven essential for reducing complications in elective surgery, particularly infection [35][36][37] . Hyperglycemia has been shown to have numerous adverse effects at the cellular level including altered chemotaxis, phagocytosis, pseudopod formation, and oxidative burst, all of which prevent neutrophils from functioning optimally [38] .…”
Section: Glycemic Control In Perioperative Periodmentioning
confidence: 99%
“…Currently, perioperative blood sugar control in both diabetic and non-diabetic patients should aim for 120-160 mg/dL to minimize complication risks [40][41][42] . Postoperative hyperglycemia remains a significant risk factor for the development of surgical site occurrences; it has been reported that even one episode of serum glucose of > 200 mg/dL increases the risk of wound dehiscence [37,43] . Strict protocols for preventing hyperglycemia and glycemic interventions have effectively reduced rates of hyperglycemia and improved outcomes [43,44] .…”
Section: Glycemic Control In Perioperative Periodmentioning
confidence: 99%
“…Early postoperative hyperglycemia (POHG) is recognized as a major cause of delays in convalescence, higher rates of complications, and increased costs of care. [1][2][3][4] The incidence of stress hyperglycemia is more likely in patients with a preoperative diagnosis of type 2 diabetes (T2D) and impaired glucose metabolism and control. [3] Strikingly, POHG has been observed among patients who are not known to have T2D.…”
Section: Introductionmentioning
confidence: 99%
“…[3] Strikingly, POHG has been observed among patients who are not known to have T2D. [1,2,[5][6][7][8] In such a cohort of patents, adverse outcomes occurring in association with POHG may be as or more consequential [1,5,7,9] than in patients with a diagnosis of T2D. Moreover, a recent study has provided seemingly paradoxical evidence that higher levels of hemoglobin A1C may be associated with a lower likelihood of post-operative complications and readmissions.…”
Section: Introductionmentioning
confidence: 99%